The Savvy Survey #17: Reporting Survey Findings - Milton G. Newberry; Jessica L. Gouldthorpe; Glenn D. Israel (EDIS)
Wrapping up the Savvy Survey Series, this fact sheet is the last of three publications that outline procedures to follow after implementing a survey. With the surveys in, data collected, and analyses conducted, the next logical step deals with communicating the results. Through communication, ideas and thoughts are shared with others in a manner that will be easily understood. In Extension, some common communication channels include the annual Report of Accomplishment (ROA), grant project reports, abstracts, and oral presentations. This 5-page fact sheet was written by Milton G. Newberry, III, Jessica L. Gouldthorpe, and Glenn D. Israel, and published by the UF Department of Agricultural Education and Communication, September 2014.